Examen Especial al Inventario de Mercaderías de la Empresa Comercial “Auto Shopping” de la Ciudad de Loja, periodo 2021. - Jiménez Pintado, Carlos Ramiro (2023)
The present project called: Special Examination to the Merchandise Inventory of the Commercial Company "Auto Shopping" of the City of Loja, period 2021; was developed as a prerequisite to opt for the Degree in Accounting and Auditing and to fulfill the objectives set out in this work of curricular integration for which it was: Evaluated the internal control implemented for the merchandise inventory component of the commercial company with the help of a questionnaire, in order to determine its compliance and qualify the level of control risk and the level of confidence; The reasonableness of the balances of the inventories component was determined with the help of the working papers and cards where the findings are summarized with their respective source documentation that supports the movements of the account; Finally, a special examination report was prepared containing comments, conclusions and recommendations to be considered by the Manager-Owner of the company. Among the main findings, it was determined that the commercial company "Auto Shopping" does not have internal regulations, a manual of functions and policies for inventory control; inventory comparisons are not made with the data provided by the ISYPLUS system; and inventory checks are not performed at least once a year, as required by internal control standards 406-10. In view of these weaknesses, recommendations were made as alternatives for improving inventory management in order to achieve the company's proposed goals and objectives.